Investigation of the impact of 'fouling out' on teams' performance in elite basketball - Gomez, M.-A.; Ortega, E.; Jones, G. (International Journal of Performance Analysis in Sport, 2016)
This study examined the impact of 'fouling out' on basketball team's performance. A sample of 237 instances of 'fouling-out' were examined from 362 elite basketball games (group and knockout games from the 2010 to 2012 men's and women's Olympic Games, European and World Championships). Variables scrutinized were: score-line, quality of opposition, time-out situation, competition stage, minutes remaining, freethrows conceded, and player status. Two linear regression models were used to analyze the temporal effects of fouling out on both the team with the offending player and the opposition. The results indicated that both teams (the 'fouling' team and the opposition) demonstrated similar positive scoring performances post 'foul-out' during in the short-term (short term effect). However, post foul-out did impact negatively on the fouling team's scoring process in the mid-term (mid-term effect). The quality of opposition variable was significant in all the analyses with negative effects for the fouling team and positive effects for the opposition. The final outcome highlighted a positive effect for the score-line (when the foul out was committed), the quality of the opposition, the competition stage, and for the time-out called by the fouling team. The results outlined implications for the coaching process such as methods for improving coaching strategies and game management of on-court players.